he “Immanuel” of Isaiah 7:14: Immediate Single Fulfillment or Distance Dual Future Messianic Prophecy? - Javien, Rico T. (11th International Scholars Conference, 2018)
The great Messianic prophecy of Isaiah 7:14 that states: “Behold, the virgin shall conceive and bear a Son, and shall call His name Immanuel.” This prophetic utterance of Isaiah regarding Immanuel has been considered difficult to be resolved. As a result, it has provoked endless controversy from both scholars from the Old Testament and the New Testament. A number of interpretative positions have been advanced by scholars from different camps and yet they have not arrived to a consensus. For instance, it was argued that the Immanuel was restricted only in the time of Isaiah, never in the New Testament. Another view holds that it was a near future in the prophet’s own time and the remote New Testament fulfilment as recorded in Matthew’s Gospel. The varied interpretations have been carefully analyzed through contextual settings and time frame factors. The study asserts that the Immanuel according to contextual analysis has dual fulfillment: first, there was immediate Immanuel at the time of the prophet Isaiah; second, the final Immanuel arrived more than seven hundred years later, when Jesus was born.